2011
DOI: 10.1371/journal.pone.0026579
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for Positive Selection on the Leptin Gene in Cetacea and Pinnipedia

Abstract: The leptin gene has received intensive attention and scientific investigation for its importance in energy homeostasis and reproductive regulation in mammals. Furthermore, study of the leptin gene is of crucial importance for public health, particularly for its role in obesity, as well as for other numerous physiological roles that it plays in mammals. In the present work, we report the identification of novel leptin genes in 4 species of Cetacea, and a comparison with 55 publicly available leptin sequences fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
36
1
9

Year Published

2012
2012
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 19 publications
(48 citation statements)
references
References 92 publications
2
36
1
9
Order By: Relevance
“…The consistency in this uncoupling across multiple species may signify a common mechanism by which metabolic expenditure is controlled in species that incorporate fasting as part of their natural history. However, we also note there is evidence that fasting-adapted penguins lack leptin activity while maintaining the tissue receptor (Yosefi et al, 2010) and that the leptin gene is under positive selection in phocids (Yu et al, 2011), suggesting the potential for unique physiological roles in this taxa.…”
Section: Discussionmentioning
confidence: 67%
“…The consistency in this uncoupling across multiple species may signify a common mechanism by which metabolic expenditure is controlled in species that incorporate fasting as part of their natural history. However, we also note there is evidence that fasting-adapted penguins lack leptin activity while maintaining the tissue receptor (Yosefi et al, 2010) and that the leptin gene is under positive selection in phocids (Yu et al, 2011), suggesting the potential for unique physiological roles in this taxa.…”
Section: Discussionmentioning
confidence: 67%
“…In humans, mutation of this gene results in a profound obesity and type II diabetes [12,[20][21][22][23]. Therefore, due to its critical role in obesity, the study of leptin will shed insight into molecular mechanism of energy homeostasis, future pharmaceutical intervention and public health [9,10,24].…”
Section: Citationmentioning
confidence: 99%
“…The leptin gene, spanning over 4.5-kb, consists of three exons and two introns [9,25]. The coding exons (exons 2 and 3) are 501 bp in length in total.…”
Section: Citationmentioning
confidence: 99%
See 1 more Smart Citation
“…The identity of the leptin protein in Xenopus to that of pufferfish, human, and tiger salamander (Ambystoma tigrinum) is 13%, 35%, and 60%, respectively [6,7,9]. Although, positive selections of leptins are revealed in several mammal lineages, for example, pikas (Ochotona curzoniae), Cetacea and Pinnipedia, and heterothermic bats [24][25][26], the conserved gene structure (three exons separated by two introns) and secondary and tertiary structures of leptins were found from teleosts to mammals [2,3,6,11,27,28]. Phylogeny reconstruction of vertebrate leptins showed that most vertebrates form distinct clades with topology consistent with the generally accepted vertebrate topology except that the relationships among teleosts remain inconsistent [2,11,29].…”
Section: Introductionmentioning
confidence: 99%